A Boolean Approach to Interactive Program Planning - Abonyi, George; Howard, Nigel (Management Science, 1980)
Program planning refers to the process of selecting an integrated set of projects for implementation. Ultimately, decisions tend to be “political” in the sense that they involve compromises and tradeoffs among different interests, though the arguments may be couched in technical terms. Program planning may be structured as a multi-stage process. One stage involves the assessment of various alternatives for the project components of the program. A second stage then involves the selection of the required program, i.e., a specific combination of project designs. This paper presents a Boolean method called Interactive Program Planning (IPP) for structuring the assessment process at the project level. The method may be used in an interactive procedure that finds which project alternatives are acceptable to different interest groups. An algorithm that identifies crucial points of disagreement between groups may then be used to help reduce disagreements, thus enlarging the set of acceptable programs. Although the focus here is on program planning, the method is of general relevance to complex issues involving collective decisions. Further, IPP implies the view that optimization methods requiring (a perhaps implicit) consensus on general objectives are of limited value as general frameworks for program planning. Instead (or in addition) the program planning process should be supported by interactive methods that can assist in achieving the widespread acceptance of specific alternatives which meet a variety of perhaps conflicting interests.